ASEAN+3 bond market guide 2016 : Singapore (ASEAN+3 bond market guide 2016 : Singapore, 2016)
Cover – Title – Copyright – Contents – Tables and Figures – Tables – 2.1 Examples of Securities Market Legislation in Each Legislative Tier – 2.2 Authorities Involved in Regulatory Processes by Corporate Issuer Type – 3.1 Characteristics of Singapore Government Securities – 3.2 Segmentation of the Market-Outstanding Value by Type of Bond or Note – 3.3 Singapore Government Securities Auction-Summary of Conduct – 4.1 Singapore Exchange Securities Trading Hours – 6.1 Monetary Authority of Singapore Enhanced Electronic Payment System Transaction Fees – 6.2 Transaction Fees of the Central Depository (Pte.) Ltd. – 6.3 Duties and Taxes on Fixed-Income Securities in Singapore – A1 Group of Thirty Recommendations-Compliance for Singapore – Figures – 1.1 Local Currency Bonds Outstanding in Singapore – 1.2 Foreign Currency Bonds Outstanding in Singapore – 2.1 Regulatory Process Map-Overview – 2.2 Offers and Prospectuses Electronic Repository and Access Homepage – 2.3 Singapore Exchange Rulebooks and Activities – 3.1 Time Line for Singapore Government Securities Mini-Auctions – 3.2 Illustration of the Singapore Savings Bonds Allotment Process – 3.3 Overview of Singapore Exchange Listing Rules for Debt Securities – 3.4 Regulatory Process-Listing on Singapore Exchange Wholesale Bonds – 3.5 Singapore Exchange Web Page for Evaluated Bond Price Service – 4.1 Singapore Government Securities Homepage – 4.2 Singapore Government Securities Prices Web Page Closing Yields – 4.3 AsianBondsOnline Web Page of Singapore Government Securities Yield Curve for Selected Periods – 4.4 Standard & Poor's Web Page of Singapore Corporate Bond Index – Foreword – Acknowledgments – Abbreviations – I. Overview – A. Introduction – B. Evolution of the Singapore Bond Market – C. Regional Cooperation – II. Legal and Regulatory FrameworkA. Legal Tradition – B. English Translation – C. Legislative Structure – D. Singapore Bond Market Regulatory Structure – E. Key Legislation and Regulations for Debt Securities – F. Debt Securities Issuance Regulatory Processes – G. Continuous Disclosure Requirements in the Singapore Market – H. Self-Regulatory Organizations in the Singapore Market – I. Registration and Licensing of Market Participants – J. Trading Rules and Conventions – K. Singapore Exchange Rules Related to Bond Listing, Disclosure, and Trading – L. Market Entry Requirements (Nonresidents) – M. Market Exit Requirements (Nonresidents) – N. Regulations and Limitations (Nonresidents) – O. Regulations on Credit Rating Agencies – III. Characteristics of the Singapore Bond Market – A. Definition of Securities – B. Types of Bonds and Notes – C. Money Market Instruments – D. Segmentation of the Market – E. Methods of Issuing Bonds and Notes (Primary Market) – F. Governing Law and Jurisdiction (Bond and Note Issuance) – G. Language of Documentation and Disclosure Items – H. Registration of Debt Securities – I. Listing of Debt Securities – J. Methods of Trading Bonds and Notes (Secondary Market) – K. Bond and Note Pricing – L. Transfers of Interests in Bonds and Notes – M. Market Participants – N. Definition of Professional Investors – O. Credit Rating Requirements – P. Financial Guarantee Institution – Q. Market Features for Investor Protection – R. Bond Trustee and Trust Deed – S. Bankruptcy Procedures – T. Event of Default and Cross-Default – IV. Bond and Note Transactions and Trading Market Infrastructure – A. Trading of Bonds and Notes – B. Tendering Platform for Singapore Government Securities (SGS eApps) – C. Trading Platforms – D. Mandatory Trade Reporting – E. Market Monitoring and Surveillance in the Secondary MarketF. Bond Information Services in Singapore – G. Yield Curves and Bond Indices – H. Repo Market – I. Securities Borrowing and Lending – J. Interest Rate Futures – V. Description of the Securities Settlement System – VI. Bond Market Costs and Taxation – A. Costs Associated with Bond and Note Issuance – B. Costs for Listing of Corporate Bonds and Notes – C. Ongoing Costs for Issuers of Corporate Bonds and Notes – D. Costs for Deposit and Withdrawal of Bonds and Notes – E. Costs for Account Maintenance – F. Costs Associated with Bonds and Notes Trading – G. Costs for Settlement and Transfer of Bonds and Notes – H. Taxation Framework and Requirements – VII. Market Size and Statistics – VIII. The Singapore Islamic Bond Market – A. Development of Islamic Finance in Singapore – B. Regulatory Approach for Islamic Finance – C. Sukuk Issuance in Singapore – D. Infrastructure for Sukuk – IX. Singapore Bond Market Challenges and Opportunities – A. Challenges in the Singapore Bond Market – B. Opportunities in the Singapore Bond Market – X. Recent Developments and Future Direction – A. Recent Major Developments – B. Future Direction – Appendixes – 1 Group of Thirty Compliance – 2 Practical References – 3 Glossary of Technical Terms